Big data concepts, technology and architecture - Balusamy, Balamurugan; Abirami. R, Nandhini; Kadry, Seifedine 1977-; Gandomi, Amir H. (Wiley, 2021)
"This book offers comprehensive coverage of Big Data tools, terminologies and technologies for researchers, business professionals and graduates. This book begins with an overview of what Big Data is and emphasizes all the key concepts of big data end to end. Big Data concepts, technologies, terminologies and storing, processing and analysis techniques and much more -- are all logically organized and reinforced by diagrams and case studies. This book refines readers' understanding of Big Data with in-depth analysis of key concepts. The case studies provided in this book give insight on key concepts. The initial chapters of the book shed light on various characteristics of Big Data that distinguish it from traditional Database Management systems. Big Data Analytics are covered in detail in a separate chapter. Hadoop, the heart of Big Data is handled in the Big Data processing chapter and a deep understanding of its concepts is provided"--
Keywords: Big Data; Big data; Data mining